Climate Variability and Water Resource Degradation in Kenya : Improving Water Resources Development and Management - Mogaka, Hezron (Washington, DC: World Bank, 2012)
This report attempts to fill that gap for two of the most important water-related issues facing the effects of climate variability and the steady degradation of the nation's water resources. The study reported here concluded that the El Niño-La Niña episode from 1997-2000 cost the country Ksh 290 billion (about 14 percent of GDP during that period). During El Niño-induced floods, this cost primarily arises from destruction of infrastructure such as roads, water supply infrastructure, and pipe networks. The largest costs incurred during the La Niña droughts (1998-2000) were from loss of industrial production and other costs arising from reduced hydropower generation, as well as from crop and livestock losses. These costs are felt throughout Kenyan society.